IMPLEMENTASI PAJAK PERTAMBAHAN NILAI (PPN) PADA PRODUK ASURANSI UMUM - Nonita Fitriani Harahap; Hayfa Azwa Fadhila; Sri Rejeki; Dini Vientiany (CV. KAMPUSA AKADEMIK PUBLISING, 2024)
Value Added Tax (VAT) is a tax imposed on domestic consumption. VAT is applied to general insurance products with the aim of increasing state revenue. VAT is imposed on insurance products sold domestically and not on insurance products sold abroad. VAT collection is carried out by VAT Collectors who have been regulated by the Decree of the Minister of Finance. VAT collectors are required to collect the tax payable at the time of payment and deposit the tax collected into the state treasury within a predetermined period of time. In analyzing the implementation of Value Added Tax (VAT) on general insurance products in Indonesia. The application of VAT to general insurance products has caused various impacts, both on insurance companies and policyholders. The implementation of VAT on general insurance products increases the cost burden for consumers, which in turn can affect the level of demand for insurance products. In addition, insurers are faced with challenges in adapting their administrative and reporting systems to comply with applicable tax regulations. However, the implementation of VAT can also increase transparency and accountability in the insurance industry.